2016
DOI: 10.1051/0004-6361/201525896
|View full text |Cite
|
Sign up to set email alerts
|

Planckintermediate results

Abstract: Within ten nearby (d < 450 pc) Gould belt molecular clouds we evaluate statistically the relative orientation between the magnetic field projected on the plane of sky, inferred from the polarized thermal emission of Galactic dust observed by Planck at 353 GHz, and the gas column density structures, quantified by the gradient of the column density, N H . The selected regions, covering several degrees in size, are analysed at an effective angular resolution of 10 FWHM, thus sampling physical scales from 0.4 to 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(11 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…Previous studies concluded that the B-fields are observed to be mostly perpendicular to the main axis of dense filaments (e.g., Planck Collaboration et al 2016a, 2016b, 2016cPattle et al 2017;Soler et al 2017;Ward-Thompson et al 2017;Liu et al 2018;Fissel et al 2019;Soam et al 2019). Three filaments in NGC 1333 (#7, #13, and #18b) show perpendicular B-field orientations, which is consistent with those studies.…”
Section: Local B-field Alignment To Filamentssupporting
confidence: 88%
“…Previous studies concluded that the B-fields are observed to be mostly perpendicular to the main axis of dense filaments (e.g., Planck Collaboration et al 2016a, 2016b, 2016cPattle et al 2017;Soler et al 2017;Ward-Thompson et al 2017;Liu et al 2018;Fissel et al 2019;Soam et al 2019). Three filaments in NGC 1333 (#7, #13, and #18b) show perpendicular B-field orientations, which is consistent with those studies.…”
Section: Local B-field Alignment To Filamentssupporting
confidence: 88%
“…Several studies show to what degree these components are connected. The Planck dust polarisation maps showed that filaments in the diffuse cold neutral medium are predominantly aligned with the local magnetic field [76], whereas filaments in dense molecular clouds are mostly perpendicular to the field [77]. This correlation between the structure of matter and that of the GMF is also observed for filamentary structures identified in spectroscopic Hi data cubes [78,79].…”
Section: Small-scale Magnetic Field Components and Interstellar Turbumentioning
confidence: 55%
“…At the same time, driven by the observational basis provided most recently by the Planck mission (Tauber et al 2010;Planck Collaboration et al 2011), the study of the observational signatures of the magnetic field with polarization is receiving renewed and heated interest in these filamentary star forming regions. While the Planck data have comparatively low angular resolution, their contribution to the discussion of filament structure through dust polarization observations is undeniable (Planck Collaboration et al 2015, 2016a.ALMA mosaic observations will be able to probe more distant and massive filaments throughout the Galaxy using both (sub)millimeter dust polarization and Zeeman line splitting observation . Already a variety of single dish results have paved the way for such observations (e.g., Matthews et al 2001Matthews et al , 2002Bertrang et al 2014;Pillai et al 2015;Pattle et al 2017).…”
Section: Introductionmentioning
confidence: 99%